2020
DOI: 10.1007/s00167-020-06160-9
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and femoral tunnel position are the most common failure modes of anterior cruciate ligament reconstruction: a systematic review

Abstract: Purpose To improve outcomes of anterior cruciate ligament reconstruction (ACLR), it is important to understand the reasons for failure of this procedure. This systematic review was performed to identify current failure modes of ACLR. Methods A systematic search was performed using PubMed, EMBASE, Cochrane, and annual registries for ACLR failures. Studies were included when failure modes were reported (I) of ≥ 10 patients and (II) at a minimum of two-year followup. Modes of failure were also compared between di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 71 publications
0
28
0
1
Order By: Relevance
“…24 Bone tunnel healing varies depending on the position in the tunnel, with healing at the aperture (the intra-articular opening) reported to be lower than that at the midportion and exit (the segment farthest from the intra-articular space). 3 The propensity for tendon-bone healing depends on the graft; hamstring tendon grafts are associated with a higher incidence of biological failures 43 and greater tunnel widening, 46 while tendon allografts have the advantage of avoiding donor-site morbidity but have delayed graft healing compared with autografts. 38 Therefore, strategies to enhance bone tunnel healing might be particularly advantageous for allogenic-free tendon grafts.…”
mentioning
confidence: 99%
“…24 Bone tunnel healing varies depending on the position in the tunnel, with healing at the aperture (the intra-articular opening) reported to be lower than that at the midportion and exit (the segment farthest from the intra-articular space). 3 The propensity for tendon-bone healing depends on the graft; hamstring tendon grafts are associated with a higher incidence of biological failures 43 and greater tunnel widening, 46 while tendon allografts have the advantage of avoiding donor-site morbidity but have delayed graft healing compared with autografts. 38 Therefore, strategies to enhance bone tunnel healing might be particularly advantageous for allogenic-free tendon grafts.…”
mentioning
confidence: 99%
“…[1][2][3] Not to suggest that the tibial position is not important, as it is, but malpositioning of the femoral tunnel has been found to be a leading cause of technical failure in ACL reconstructions. 4 So, the issue is how we best make our ACL femoral socket? Certainly, this topic has been well researched, 5 but now authors Moorthy, Sayampanathan, and Tan in their article "Superior Postoperative Stability and Functional Outcomes With Anteromedial Versus Transtibial Technique of Single-Bundle Autologous Hamstring Anterior Cruciate Ligament Reconstruction: A Meta-analysis of Prospective Randomized Controlled Trials" have provided us with further evidence of the benefit of anteromedial (AM) portal drilling.…”
Section: See Related Article On Page 328mentioning
confidence: 99%
“…6,18,30 The annual reported incidence of ACL tears is 68.6 per 100,000 person-years and peaks between 19 and 25 years in male patients and between 14 and 18 years in female patients. 30 Many studies 6,7,9,24,31,37 have identified factors that affect the outcomes of ACLR. Some studies 8,16,26 have suggested that anatomic ACLR is preferred over nonanatomic ACLR (isometric).…”
mentioning
confidence: 99%